THE CRECHE AS A PLACE FOR THE TEACHING OF TEACHERS IN CHILDREN EDUCATION - Márcia Regina Onofre; Andressa de Oliveira Martins; Cleonice Maria Tomazzetti (Universidade Estadual Paulista Júlio de Mesquita Filho, 2017)
The objective of this research was to analyze the reflections from participants of an extension project of UFSCar related to the signification and re-signification of teacher identity process. This study was developed in the perspective of contribution from the school as a locus of continuing training, experience sharing, knowledge and practices. Qualitative approach was used in the study. Data were collected during Extension Project in 2013 and 2014, and they were organized from four categories: profile of the teachers participating in the research; vision of the teachers about the profession; work in early childhood education and teacher training; reflections during the process of ressignification of the teacher/teaching identity. Results indicated that continuing education is an essential learning space for the construction of teacher identity ressignification, as well as allows a greater visibility of the teacher as a professional, and social recognition for teachers, especially those working in early childhood education.